Dye‐Conjugated Spinach RNA by Genetic Alphabet Expansion. Issue 16 (24th February 2022) - Hyun Lee, Kyung; Kimoto, Michiko; Kawai, Gota; Okamoto, Itaru; Fin, Andrea; Hirao, Ichiro
Abstract: Light‐emitting systems using an RNA aptamer‐dye pair, such as Spinach RNA, are an attractive method for imaging and tracing RNA expression in vitro and in vivo . We present an alternative Spinach method by genetic alphabet expansion using an unnatural base pair system, in which a dye‐conjugated unnatural base substrate is site‐specifically incorporated at a specific position in Spinach RNA by transcription involving the third base pair. The incorporation position was predicted by molecular dynamics simulations. This dye‐conjugated Spinach RNA increased the thermal stability of the fluorescence, the robustness against ion sensitivity, and the resistance against photobleaching. Furthermore, we applied our method to Baby Spinach, a shorter version of Spinach, for dye conjugation toward the visible detection of transcripts. This is the first demonstration of an alternative RNA imaging method for a detection system using genetic alphabet expansion. Abstract : Light emission by dye‐conjugated Spinach RNA transcripts can be generated by genetic alphabet expansion. Dye‐conjugated unnatural base substrates are site‐specifically incorporated into Spinach RNA opposite to its unnatural base pairing partner in DNA templates by T7 transcription. The dye‐conjugated Spinach RNAs or shorter versions robustly emit fluorescence.